AN OVERVIEW ON TASTE PHYSIOLOGY AND MASKING OF BITTER DRUGS - SWARNIMA PANDEY; SUSHANT KUMAR; S.K.PRAJAPATI; N.V.SATHEESH MADHAV (International Journal of Pharma and Bio Sciences, 2010)
Taste is an important parameter in administering drugs orally. Undesirable taste is one of the important formulation problems that are encountered with many drugs. The bitterness of human pharmaceutical medicines plays a critical role in patient compliance as the oral administration of bitter drugs is often hampered by their unpleasant taste, leading to noncompliance and thus decreasing therapeutic efficacy, especially in case of children and the elderly. In this review, we discuss about anatomy and physiology of taste buds and taste papillae, Taste transduction, taste receptor, Artificial Sweetner, Taste Masking Technologies. This review will help pharmaceutical formulation researchers and other relevant scholars to make use of this towards palatable foods or medicines.